Introduction of a new health technology into a provincial health system: A case study of insulin pump therapy. Issue 5 (September 2015) - Menon, Devidas; Stafinski, Tania; Nardelli, Alexa; Edwards, Alun
Decisions on the introduction of new non-drug health technologies into healthcare are challenging. This article describes the introduction of insulin pump therapy for type 1 diabetes in Alberta, using an Access with Evidence Development (AED) approach. The organization and implementation of the AED, its current status, and lessons learned are described.